A new species of Tingidae from Cretaceous amber from Myanmar (Hemiptera, Heteroptera) - Heiss, Ernst; Guilbert, Eric (Zootaxa, 2018)
From the Upper Cretaceous Burmese amber, only three genera and species of Tingidae, (Spinitingis ellenbergeri and Burmacader multivenosus Heiss & Guilbert, 2013; Tingiometra burmanica Heiss et al. 2015), are reported to date. A new species Burmacader lativentris sp.nov. is described and illustrated.